Hubungan Antara Regulasi Diri dengan Prokrastinasi Akademik pada Mahasiswa Korps Sukarela Palang Merah Indonesia (KSR PMI) di Universitas Negeri Padang - Lidia Nisva; Ria Okfrima (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2019)
This research was carried out to PMI KSR students in Padang State. This study aims to see whether there is a relationship between Self Regulation and Academic Procrastination at Students of the Voluntary Corps of the Indonesian Red Cross (KSR PMI) at Padang State University. The population in this study was the 2014 PMI KSR students who were still active in the organization. The research subjects used Purposif sampling technique. Sampling technique with certain considerations. Measuring instrument used is the self-regulation skla researchers collated based on the theory proposed in 2014 and Procrastination Purnawasari the researchers collated based on the theory proposed by Gufron 2010. Data analysis methods were used to test the hypothesis in this research is by using correlation product moment(person)which shows that r = -0,378 with a value of p = 0.016, meaning that there is a significant relationship between the relationship between self-regulation and the 2014 KSR PMI student procrastination at Padang State University. Means the research hypothesis is accepted. The effective contribution of the self-regulation variable with the 2014 PMR KSR student academic procrastination in Padang is 14%.